Cross-sectional Study: User satisfaction related of Chilean Government`s food hampers for Covid-19 - Rodríguez-Palleres, Ximena (2021)
The COVID-19 pandemic identified in December 2019 has not only negatively impacted people's health, but also global economies. Chile has implemented a series of measures to combat the economic crisis resulting from the health emergency, one of them is food aid. Objective: Determine the user satisfaction related to the supply of food boxes distributed by the Government in Chile as a result of the Covid-19 pandemic. Materials and methods: Descriptive observational cross-sectional study. 485 (365 women and 120 men) inhabitants of Santiago de Chile were recruited. An online questionnaire consisting of five items was designed. Results: The food box received an average acceptability of 5.1 out of 7 points rated as “good”. 85.5% of the participants consider that the food contained in the boxes is a basic necessity. 31.9% fully agreed that the food delivered is a support to the households. At least a quarter of users (20.7%) consider that the food box helped them go to the supermarket less frequently. While only 14.2% declared they totally agree that the boxes cover nutritional needs. Conclusions: Knowing the beneficiaries' perception of food aid as part of a government program provides timely information that allows them to be improved in the face of future health, environmental and / or economic crises.